Rural poverty dynamics in Kenya: Structural declines and stochastic escapes - Radeny, Maren A.O.; Berg, M. van den; Schipper, R (Elsevier, 2012)
We use panel survey data and household event-histories to explore patterns of rural poverty dynamics in Kenya over the period 2000–2009. We find substantial mobility across poverty categories using economic transition matrices. Drawing on asset-based approaches, we distinguish stochastic from structural poverty transitions. Few households successfully escaped poverty through asset accumulation (up to 35% of the upwardly mobile), while a large proportion of households (up to 66%) declining into poverty experienced structural transitions. Using household event-histories, we find significant differences across structural poverty transition classes in livelihood strategies, household-level shocks, and other factors.